Sistema de Monitoramento Inteligente da COVID-19 em SP - Santos, Alessandro S.; Teixeira, Igor C.; Avanço, Leandro; Neves, Rodrigo; Gonçales, Icaro; Inacio, Angelina (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia); 2021: Anais Estendidos do XXVII Simpósio Brasileiro de Sistemas Multimídia e WebDO - 10.5753/webmedia_estendido.2021.17619, 2021)
São Paulo was one of the first states affected by COVID-19 in Brazil. The Intelligent Monitoring System (SIMI) was an important milestone to face the pandemic, whose mission was to consolidate and integrate data on vehicular and people mobility, epidemiological situation, and economic status to support the state government in its strategic decisions. Overcoming the challenges of integration, anonymity, privacy, and multidisciplinarity were essential to provide results for analyzing scenarios and better information for decision-making. SIMI indicators impacted the entire São Paulo society, which defined criteria for flexibilization or restriction of economic sectors or supporting strategic changes to face the pandemic.